PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR CONSUMER NON CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 – 2022 - Yuli Astutik; Suhesti Ningsih; Hadi Samanto (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This research aims to analyze the profitability, liquidity and solvency of share prices in non-cyclical consumer sector companies listed on the IDX for the 2020 - 2022 period. Sampling used purposive sampling with time series data to obtain a sample of 93. The method in this research uses a test. Descriptive statistics, classical assumption tests, and hypothesis testing with the F test (model feasibility test), t test and R2 test. The results of the F test obtained a significance value of 0.003 < 0.005, so the model is suitable for use. This means there is no need to vary the model in research. From the results of the hypothesis test, the test shows that the profitability variable has an effect on share prices, this is proven by the significance value of 0.00 i<0.005. Meanwhile, the liquidity and solvency variables have a significance value greater than 0.05, namely 0.792 and 0.253, thus it can be concluded that liquidity and solvency have no effect on share prices. From the R2 test results, the customized R isquare value is obtained of 0.389 or 38.9%. This shows that the variables profitability, liquidity and solvency can influence share prices by 38.9%. Meanwhile, the remaining 61.1% was influenced by other factors outside the research.